Capitalisation of residential solar photovoltaic systems in Western Australia1. (29th September 2015) - Ma, Chunbo; Polyakov, Maksym; Pandit, Ram
Abstract : Due to government financial incentives and falling prices of photovoltaic (PV) systems, solar power has become the fastest growing renewable energy source in Australia. As financial incentives are being reduced or phased out, there is a possibility that adoption of this technology will slow down, thus creating a need for improved policy instruments targeted at adoption of residential PV systems. One of the factors affecting adoption of solar technology in the residential sector is its capitalisation in property values. Yet, the awareness of the capitalisation of PV investments in the Australian property market is limited. Our data indicate that homeowners who anticipate selling their properties in the near future are reluctant to adopt PV systems. This paper presents the first empirical estimate of the property price premiums associated with residential solar PV systems in Australia using residential property sales data from the Perth metropolitan area of Western Australia. An estimated 2.3–3.2 per cent property price premium associated with the PV systems suggests that homeowners fully recover the costs of PV investments upon the sale of their properties. Effective government policy could use this information to encourage adoption of residential PV systems by homeowners.